THE IMPACT OF SOME TRAITS PROVIDING TOLERANCE TO PESTS IN COTTON IN CREATING A CLEAN ECOLOGICAL ENVIRONMENT - Umarova Jumagul Kuziyevna (Modern American Journals, 2025)
The hybridization of the lines of the wild polyploid species of cotton growing in the Hawaiian Islands, G.tomentosum Nutt. ex Seem. and G.hirsutum L., was carried out using the lines isolated as a result of a single selection from the interspecific hybrids obtained by crossing them, and the L-001 analyzer line of G.hirsutum L., and the study of the importance of certain traits providing tolerance to cotton pests in the generations in creating a clean ecological environment, that is, the study of the nature of inheritance of the type of hairiness on the leaves of hybrids, and the genetic analysis of their variability are described.
Keywords: cotton, pure ecological environment, wild polyploid species G.tomentosum Nutt. ex Seem., G.hirsutum L. species, hybridization, L-001 analyzer ridge, leaf hair type, nature of inheritance.